Intrauterine Environment and Polycystic Ovary Syndrome - Dumesic, Daniel A.; Goodarzi, Mark O.; Chazenbalk, Gregorio D.; Abbott, David H. (Seminars in Reproductive Medicine, 2014)
The maternal–fetal environment plays an important role in developmental programming of adult disease. Metabolic and hormonal dysfunction during human fetal development accompanies gestational diabetes as a common occurrence in mothers with polycystic ovary syndrome (PCOS), while human fetal androgen excess from congenital adrenal hyperplasia or virilizing tumors precedes PCOS-like symptoms after birth. To date, clinical studies of infant blood levels at term have yet to confirm that human fetal androgen excess promotes PCOS development after birth. Earlier in development, however, circulating androgen levels in the second trimester female human fetus can normally rise into the male range. Furthermore, midgestational amniotic testosterone levels are elevated in female fetuses of PCOS compared with normal mothers and might influence fetal development because experimentally induced fetal androgen excess in animals produces a PCOS-like phenotype with reproductive and metabolic dysfunction. Such alterations in the maternal–fetal environment likely program adult PCOS by epigenetic modifications of genetic susceptibility of the fetus to PCOS after birth. Understanding this phenomenon requires advanced fetal surveillance technologies and postnatal assessment of midgestational androgen exposure for new clinical strategies to improve reproduction in PCOS women, optimize long-term health of their offspring, and minimize susceptibility to acquiring PCOS in future generations.
Keywords: polycystic ovary syndrome; hyperandrogenism; hyperinsulinemia; adiposity; developmental programming; fetal development